Development of Android-Based Network Service Technology Learning Media for Vocational Middle School Students - Helmiza Helmiza; Dedy Irfan; Asrul Huda (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Information and communication technology have developed along with globalization so that interaction and information delivery will quickly. One of the problems in education that is a priority to immediately find a solution is the problem of the quality of education, especially the quality of learning. From various existing conditions and potentials, efforts that can be made regarding quality improvement in schools are to develop a student-oriented learning system (children center) and facilitate students' needs for learning needs that are challenging, active, creative, innovative, practical, and fun with developing and implementing Information and Communication Technology-based learning This research is a Research and Development research with the media development model used referring to the type of Four-D development consisting of 4 stages, namely Define (defining), Design (design), Develop (development) and Disseminate (dissemination) which is carried out in Vocational High School class XI Computer and Network Engineering. The test subjects in this study were students of class XI Computer and Network Engineering SMK. The results of the three validators' overall assessment of the validator test assessment of Android-Based Learning Media is 94.28%, so the level of validity can be interpreted as Very Valid for use. Overall, the practicality assessment of Android-Based Learning Media as a learning resource is 88.46%, so the practicality level can be interpreted as Very Practical to use. As well as the assessment of the effectiveness of the Android-Based Learning Media of 90.86%, so that the level of effectiveness can be interpreted as very good for use.